A comparison of training and competition physical demands in professional male basketball players - Rubén Portes; Carlos Ribas; Adrián López García; Enrique Alonso Pérez-Chao (Universitas Majalengka, 2023)
The main aim of this study was identifying differences in physical load between training and match-play. Twelve professional basketball players were monitored during 5 games. The following workload variables were recorded: Movement load (ML), Training Impulse (TRIMP), average Heart Rate (HR). Non-significant differences were found between activities (game vs practice). Regarding to practical meaningfulness, greater match values were reached for EL and IL variables compared to practices. In this regard, large differences for ML (F = 0.71, ES = 1.69) and TRIMP (F = 0.02, ES = 1.71, large) were found. In conclusion, greater values of physical load but non-significant differences were achieved during games compared to practice for ML, TRIMP and HR. In this regard, physical demands remain consistent (large effects) regardless of activity (game vs practice) in professional basketball players.